2021
DOI: 10.1021/acs.analchem.1c03834
|View full text |Cite
|
Sign up to set email alerts
|

Sonochemiluminescence Using Apertureless USB Piezoelectric Ultrasonic Transducer and Its Applications for the Detection of Hydrogen Peroxide, Glucose, and Glucose Oxidase Activity

Abstract: The mesh-type USB piezoelectric ultrasonic transducer (USB-PUT) used in household humidifiers and inhalation therapy devices is very cheap, small, and energy saving. It holds great promise for sonochemistry. However, the microtapered apertures in the center of the stainless steel substrate of mesh-type USB-PUT can lead to rapid atomization of solution, leakage of solutions containing surfactants and organic solvent through the apertures, and high background emission. Herein, we design a new type of USB-PUT by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…However, it was operated with a power of 45–50 W, and its coupling with ICP-QMS for sample analysis has not been reported . Recently, low-frequency and miniaturized ultrasonic nebulization (MUN) has received increasing attention and achieved extensive applications. , Notably, MUN is an ultra-cheap (less than $1) and readily available device compared to other expensive sample introduction systems and has been used as an efficient sample introduction unit for a soft ionization source , and microplasma excitation source . In addition, it is also used in the sample preparation of matrix-assisted laser desorption ionization (MALDI) because of the uniform and smaller aerosol-particle production capability and the elimination of the carrier gas .…”
Section: Introductionmentioning
confidence: 99%
“…However, it was operated with a power of 45–50 W, and its coupling with ICP-QMS for sample analysis has not been reported . Recently, low-frequency and miniaturized ultrasonic nebulization (MUN) has received increasing attention and achieved extensive applications. , Notably, MUN is an ultra-cheap (less than $1) and readily available device compared to other expensive sample introduction systems and has been used as an efficient sample introduction unit for a soft ionization source , and microplasma excitation source . In addition, it is also used in the sample preparation of matrix-assisted laser desorption ionization (MALDI) because of the uniform and smaller aerosol-particle production capability and the elimination of the carrier gas .…”
Section: Introductionmentioning
confidence: 99%
“…Phthalhydrazide derivatives provide a series of chemiluminescence (CL) substances for bioimaging and biochemical analysis. Among all, luminol (3-aminophthalhydrazide) is the best-known and most widely used chemiluminogenic small molecule due to its easy preparation and relatively stronger luminescence. In forensic science, for example, luminol reagents are often used to identify and image bloodstains over other colored substances. In addition, luminol is extensively used in enzymatic chemiluminescence immunoassay (CLIA) by serving as a CL substrate to horseradish peroxidase (HRP). Nevertheless, the application of luminol is still suffering from some drawbacks, such as short emission wavelength, low quantum yield, and poor structural tunability. Previous studies have found that the heterocycle has limited tolerance to chemical modification, for instance, alkylation on the heterocycle ring can suppress CL completely .…”
Section: Introductionmentioning
confidence: 99%
“…37 Piezoelectric semiconductors with wurtzite structures possess the properties of piezoelectricity and semiconducting simultaneously, and are very useful in making piezotronic transistors, in which the electronic transport is controlled by inner-crystal potential. [38][39][40] Based on piezoelectronics, devices such as mechanical sensors, 41,42 ultrasonic transducers, 43,44 energy harvesters, [45][46][47] robots and actuators [48][49][50] have been widely applied in bioelectronics and biomedical fields recently. The effect of piezoelectronic electrons from piezoelectric materials on cells and tissues is similar to that of bioelectricity and an external EF.…”
Section: Introductionmentioning
confidence: 99%